Students’ Inspiration in Making Short Story Projects in English Writing Class: English - Chusnul Chotimah; Euis Meinawati; Chodidjah Chodidjah (Journal of English Development, 2025)
This study aims to examine the factors that inspire students to complete short story projects in English writing classes. The qualitative descriptive method is a research method that combines descriptive and qualitative research. This method is used to describe phenomena, events, or conditions socially. The research activities were carried out in the odd semester English writing class of the 2024-2025 academic year, English study program, at Bina Sarana Informatika University, Jakarta. The participants involved were 35 semester III students. The data collection techniques used include: In-depth interviews, Focus groups, Observation, and Documentation. The data analysis technique consists of three steps, namely data reduction, data presentation, and conclusion. The analysis results concluded that personal experiences, films, YouTube, novels, and peer experiences are the main sources for students in completing short story project assignments. Students can get the idea to write the short story from them. It means that the teacher must know the media of learning in writing class especially to give the task of short story project so that students can use the inspiration in writing. This finding explains that educators must teach a comprehensive understanding of the essence of the material to students.